THE IMAGE MEDIA IMPROVES LEARNING INTEREST IN CLASS XI STUDENTS IN MA. MIFTAHUL MIDAD LUMAJANG - Linda Ayu Norna Sari (Mastery: Master of English Language Journal, 2022)
Learning media in the form of pictures is a tool for the teachers in the learning process. They use it to form meaningful learning for students. So the role of a teacher with the expertise, accuracy, and ability to use the media is very influential in the formation of learning interest in students. This research aims to describe the use of picture media in increasing the interest in learning for XI class students at MA.Miftahul Midad Lumajang. This type of research is a qualitative study in which the researcher describes the use of image media increasing the interest in learning XI class students. The research subjects were 21 XI class students at MA.Miftahul Midad Lumajang. The data analysis technique is the flow, which includes data reduction, data presentation, and verification stage. The results showed that the teacher’s strategy in using picture media increased the learning interest of XI class students at MA. Miftahul Midad Lumajang: adjusting the material with the pictures to be used, designing media images, adjusting learning steps based on lesson plans, and referencing a learning objective that has been prepared previously.